Marriage Taboos in the Month of Suro for The Batur People Village, Getasan Regency, District of Semarang - Muhammad Fahrizal Hakim (QURU’: Journal of Family Law and Culture, 2023)
Javanese tradition has many customs, one of which is the abstinence from marriage in the month of Suro (Muharram). This custom also applies to the people of Semarang Regency, Central Java.  The month of Suro is a very sacred month, this tradition is still held firmly by the people in Central Java, so that people do not have the courage to hold an event, especially a wedding celebration. If you insist on doing a wedding in that month, it can be said to violate a Javanese tradition, so that it will cause misfortune and misery for the bride and groom in navigating the household ark. This research is classified as empirical research. The purpose of this article is to reveal what is behind the prohibition of marriage in the month of Suro and what the restrictions and risks are. This research approach is a case study approach.  The data analysis method used is qualitative data analysis. The Javanese traditional community believes that organizing a wedding in the month of Suro is a day that brings bad luck or bad luck, which when examined through the interview process to community leaders there is no religious rule that prohibits getting married in the month of Suro. The conclusion of this article is that the community still believes in the customs that have existed since the time of the ancestors until now. The community also still marks that the month of Suro is not good for doing anything.